Pengaruh Kualitas Produk dan Desain Produk terhadap Kepuasan Konsumen Srimelanting Decoration di Ubud - Cahyadi, Komang Gde Tris; Putu Kawiana, I Gede; Dewa Ayu Yayati Wilya Dewi, Ida I (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Every business must have an orientation towards customer satisfaction because of the intense competition that occurs as more and more producers participate in meeting consumer needs and aspirations. Various elements, including product design and quality, impact consumer happiness. The aim of this research is to determine the relationship between product design and quality and the level of satisfaction experienced by customers at Srimelanting Decoration. An approach known as quantitative research techniques was used for this research. The Srimelanting decoration was used as a research location. Customers who have purchased Srimelanting Decorations are included in the research population, and the sample size for this research is eighty people who have responded to the survey. Several validity and reliability tests, as well as classical assumption tests, coefficient of determination, t test, and F test were used in the analysis of this research data. So be it. The research results show that customer happiness is significantly influenced by product quality. Moreover, product design significantly influences customer happiness in a beneficial way. The percentage is 66.8% based on product quality and design.